Architectural design in 1890s Wellington cityscapes - Humphris, Adrian (Architectural History Aotearoa, 2023)
In the absence of landscape architecture as a profession the aggregation and location of architects (and local authority engineers) directly impacted cityscapes where they practiced. As well as the built environment other factors were significant in shaping the cityscape, such as the distribution of population growth, regulation of subdivision and road construction, and land sale practices of the time. The late nineteenth century was a period over which the architectural profession was beginning to consolidate. While still lacking formal structure and regulation, meaning the individuals involved possessed a range of experience, knowledge and ability, architects increasingly became professional office workers with well-staffed offices capitalising on the demand for construction. Using Wellington as a case study, this paper uses local authority building permit records and other sources to determine the location and patterns of architecturally-designed dwellings in the city’s streetscapes. Findings suggest that architect’s impact on the urban form varied considerably across the city.